First Eneolithic Idol Finds in Dalmatia (Archaeologia Adriatica, 2009)
The article deals with two unique finds of Eeneolithic acephalic idols unearthed in the course of excavations in 2010 at the Buković − Lastvine site in Benkovac near Zadar. The idols have been only partly preserved. They were found close to each other in a very shallow pit on the very inner edge of a larger pit structure, but outside of any ritual context. They belong to a safe stratigraphic context composed of channelled pottery characteristic of the early Eneolithic in the eastern Adriatic.
Keywords: Eneolithic; Eneolithic idols; Benkovac; Buković − Lastvine